2020
DOI: 10.1108/jhr-07-2019-0161
|View full text |Cite
|
Sign up to set email alerts
|

Testing the efficacy of a brief-caries risk assessment form to evaluate the dental health status among preschool children, Bangkok, Thailand

Abstract: PurposeThe study aims to test the efficacy of brief-caries risk assessment form with standard caries risk assessment form and to evaluate the application of caries risk assessment following American Academy of Pediatric Dentistry (AAPD) between brief and standard caries risk assessment on dental health status among preschool children.Design/methodology/approachBrief-caries risk assessment form was developed. Then, experimental study was conducted in public health center 54 among 70 patients (35 test and 35 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The present systematic review and meta-analysis is one of its kind to represent oral health behavioral changes in children as an effect of MI compared to traditional health education among children's mothers. Overall, the quality of studies included in the review ranged from low to high risk as assessed with the Cochrane ROB tool results in significantly favoring MI, which were reported in five studies by Mohammadi et al, 22 Nomaire et al, 21 Manchanda et al, 18 Colvara et al, 16 Naidu R et al 19 while in one study Gonzalez et al 17 reported that MI is an effective and promising technique for establishing preventive behaviors, another study by Weinstein et al 9 reported that MI enhanced the preventive behavior of mothers of young children at high risk of developing caries, yet another study by Saengtipbovorn et al 20 demonstrated that combination of MI and caries risk assessment in one program, decreased early childhood caries in preschool children. The review reported only one study by Ismail et al 15 that did not favor MI and signified that a single MI intervention might change some reported oral health behaviors, but it failed to reduce the number of new untreated carious lesions among children.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The present systematic review and meta-analysis is one of its kind to represent oral health behavioral changes in children as an effect of MI compared to traditional health education among children's mothers. Overall, the quality of studies included in the review ranged from low to high risk as assessed with the Cochrane ROB tool results in significantly favoring MI, which were reported in five studies by Mohammadi et al, 22 Nomaire et al, 21 Manchanda et al, 18 Colvara et al, 16 Naidu R et al 19 while in one study Gonzalez et al 17 reported that MI is an effective and promising technique for establishing preventive behaviors, another study by Weinstein et al 9 reported that MI enhanced the preventive behavior of mothers of young children at high risk of developing caries, yet another study by Saengtipbovorn et al 20 demonstrated that combination of MI and caries risk assessment in one program, decreased early childhood caries in preschool children. The review reported only one study by Ismail et al 15 that did not favor MI and signified that a single MI intervention might change some reported oral health behaviors, but it failed to reduce the number of new untreated carious lesions among children.…”
Section: Discussionmentioning
confidence: 91%
“…Risk of bias (ROB) as assessed by the Cochrane ROB tool revealed that one study by Saengtipbovorn et al 20 was of low risk, two studies reported by Nomaire et al 21 , Manchanda et al 18 were of moderate risk, while six studies by Gonzalez et al, 17 Weinstein et al, 9 Naidu et al, 19 Mohammadi et al, 22 Colvara et al, 16 and Ismail et al 15 were of high risk ( Fig. 4 ).…”
Section: R Eview R Esultsmentioning
confidence: 99%